Development of Pterintifier (Pteridophyta Identifier) Based on as a Learning Source and to Train Digital Literacy for 10th Grade in Senior High School - Afifah Al Faizah; Wisanti Wisanti (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2022)
Digital literacy is a student's ability that must master in the 21st century. One of the efforts to practice digital literacy is to use social media as a learning resource. Pterintifier (Pteridophyta Identifier) ​​uses Instagram as a learning resource with the account name Pterintifier.id, presenting information on ferns. The purpose of this study is to produce a Pterintifier as a learning resource for the diversity of ferns to practice digital literacy that is feasible theoretically, empirically, and effectively. This study uses a 4D model without the stage of being disseminated. The pterintifier eligibility parameters are based on validation results from 3 validator (botanist, education expert, biology teacher), student responses, and user effectiveness. The research instruments are validation assessment instruments, student response questionnaires, and the point of the Pterintifier. The validation assessment includes aspects of content, presentation, learning resources, and digital literacy, while the response questionnaire consists of 20 statement items related to aspects of concept presentation and physical presentation. The data analyzed by descriptively quantitatively. The results showed that the validity of the Pterintifier was 3,69 (very valid). The effectiveness of Pterintifier to train digital literacy based on student success and student responses. Based on the success of using the Pterintifier, the results were 98,3 (very good), and positive student responses were 98,3 (very good). Thus, this development research resulted in the Pterintifier as a theoretical, empirical, and effective learning resource as learning resource for fern diversity to practice digital literacy. Keywords: Instagram, learning souce, digital literacy, fern diversity.